Investigation into dog bite in cattle, goats and dog at selected veterinary hospitals in Bangladesh and India - Islam, Kazi Muhammad Fakhrul; Hossain, Md Iqbal; Jalal, Shah; Quader, Md Nurul; Kumar, Saroj; Islam, Kamrul; Shawn, Ashif Imtiaz; Hoque, Ahasanul (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The study was conducted to estimate the proportionate prevalence of dog bite in cattle, goats and dog at selected veterinary hospitals in Bangladesh and India, and to assess the farmers knowledge level about dog bite and rabies in general. Materials and methods: A 4-month prospective study was conducted to evaluate the prevalence of dog bite in different species at selected veterinary hospitals in Bangladesh and India during January to July 2015. A total of 119 dog bite cases were identified by anamnesis, manifesting signs and clinical and physical examinations. Information about site of bite, duration, bite management, vaccination history, rabid dog, breed, age, sex and knowledge about rabies were composed by extensive cross-questioning to the farmers using pre-structured questionnaire. Results: The proportionate prevalence was found higher in goats (25.7%) irrespective of study placements. Hind leg (28-50%) and hind quarter (13-34%) of all species were found as the most vulnerable body part for dog bite. Younger (8-26%) and female (6-36%) animals were more prone to attack by dog. About 65% farmers had preliminary knowledge about rabies and they were aware about high fatality rate of this disease. Most of the respondents (about 45%) said that they did not know about how many days required to occur rabies after the animal being bitten by a rabid dog. Around 70% people had knowledge about source of rabies vaccine, and 74% people thought that the Government Veterinary Hospital was the main source of post exposure rabies vaccine. After dog biting, out of 119, 106 victims were recovered as a result of proper washing and dressing of biting site, and administration of post exposure rabies vaccine. Conclusion: Dog bite was higher in younger and female animals as compared to males and adult animals with an exception in case of dog. http://doi.org/10.5455/javar.2016.c167